Mobile application-based monitoring in post-breast reconstruction surgery: current trends and future directions - Jae Hoon Jeong (Archives of Aesthetic Plastic Surgery)
Mobile apps are frequently utilized in various medical fields for postoperative care, yet there is limited research concerning their application among breast reconstruction patients. This paper examines the development of mobile apps for postoperative care and discusses key considerations for their design and implementation in the context of breast reconstruction patients. Mobile apps provide a holistic approach to recovery, featuring personalized recovery plans, wound monitoring, pain tracking, medication management, virtual consultations, and emotional support. These functionalities improve patient outcomes, facilitate communication between patients and healthcare providers, and enhance engagement with the recovery process. Advanced digital healthcare technologies are revolutionizing patient care, particularly in home settings, by improving monitoring capabilities and telemedicine, thus increasing access and efficiency. For mobile apps to be successfully adopted in postoperative care, it is crucial to address regulatory, financial, and engagement challenges to ensure they deliver sustained value to both patients and healthcare providers. Future research should aim to extend these solutions to plastic surgery and other medical disciplines to improve recovery outcomes for a broad range of patient populations.